(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Occurrence of large carnivores in island ecosystems is unusual, especially in the case of top predators. Here, a new endemic hyaenid species, Chasmaporthetes melei, from the late Late Pliocene to earliest Pleistocene fissure fillings of Monte Tuttavista, Orosei, Sardinia, is described. Although smaller, C. melei is morphologically comparable with the Plio-Pleistocene Eurasian hunting-hyena Chasmaporthetes lunensis, a possible ancestor of the Sardinian species. C. melei displays all the characteristic feeding adaptations of Chasmaporthetes, including a derived enamel structure similar to the condition in extant bone-crushing hyaenas. C. melei was an active predator that nonetheless included a relatively large amount of bone in its diet. SHORT NOTES